Peran Dinas Kebudayaan Dan Pariwisata Kota Tanjungpinang Dalam Ajang Anugerah Desa Wisata Indonesia (ADWI) Studi Kasus: Pulau Penyengat Kota Tanjungpinang - Diah Ayu Sholeha; Desma Tri Anggriani; Mellyana Candra (Jurnal Ekonomi, Manajemen Pariwisata dan Perhotelan, 2024)
Penyengat Island is included in the cultural tourism destinations in Tanjungpinang City, which is located in Tanjungpinang District, Riau Islands Province. There is a very strong religious tourism on Penyengat Island, one of which is pilgrimage tourism. Penyengat Island also has heritage buildings from the Riau Lingga Kingdom, Malay arts, gurindam 12, and customs that are still strong in their authenticity. The aim of this research is to look at the role, challenges and follow-up of the Tanjungpinang City Culture and Tourism Department in winning Penyengat Island at the "ADWI" Indonesian Tourism Village Award event. This research uses qualitative descriptive research. From the results of this research, it was found that the role carried out by the Disbudpar is to include it by registering Penyengat Island in the "JADESTA" Tourism Village Network application, the challenge is to apply a tourism conscious spirit to the people of Penyengat Island and digital marketing is a follow-up carried out by the Disbudpar in promoting Penyengat Island through the media social and determined through the Decree of the Mayor of Tanjungpinang Number 126 of 2023 concerning the Designation of Penyengat Island as a Tourist Village in Tanjungpinang City.